The Correlation Between The Needs and Expectations of The Private Sector Employees and Their Media Consumption To Receive Needs Gratification - Pawiro, Adagracia Srisoesiatie; Dwiningtyas, Hapsari (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The Ministry of Labor, Work Employment and Youth Affairs of Suriname is responsible for, among other things employment, good industrial relations, labor protection, protection of the employees, and decent work. This ministry has a communication department that is sharing information about labor issues through the media. But there are still questions coming in daily about labor issues. Based on these questions, the workforce that is 54.2% of the total population of Suriname, and also giving substance to the importance of effective communication and dissemination of labor market information, it is important to understand what information has to be provided. To understand which information is needed to be provided and to use the preferred media channels, the Uses and Gratifications Theory is applied to this study. This research has several findings such as the need for specific information is the highest, the media is meeting the expectations more for general information than the specific information, online media use is very high and the media fulfillment for general needs is higher than for the specific information that the respondents need, although the need for specific information is higher.